Naturally Occurring Genetic Variants of Human Caspase-1 Differ Considerably in Structure and the Ability to Activate Interleukin-1β - Luksch, Hella (2013)
Caspase-1 (Interleukin-1 Converting Enzyme, ICE) is a proinflammatory enzyme that plays pivotal roles in innate immunity and many inflammatory conditions such as periodic fever syndromes and gout. In- flammation is often mediated by enzymatic activation of interleukin (IL)-1β and IL-18. We detected seven naturally occurring human CASP1 variants with different effects on protein structure, expression, and enzymatic activity. Most mutations destabilized the caspase-1 dimer interface as revealed by crystal structure analysis and homology modeling followed by molecular dynamics simulations. All variants demonstrated decreased or absent enzymatic and IL-1β releasing activity in vitro, in a cell transfection model, and as low as 25% of normal ex vivo in a whole blood assay of samples taken from subjects with variant CASP1, a subset of whom suffered from unclassified autoinflammation. We conclude that decreased enzymatic activity of caspase-1 is compatible with normal life and does not prevent moderate and severe autoinflammation.